Makam Keramat Datuk Tongah: Pembacaan Etnografis Akademisi Pelaku Ziarah - Muhammad Yaser Arafat (UIN Sumatera Utara Medan, 2021)
Keramat Datuk Tongah is consisted of two ancient grave located in Masjid Al-Mukarramah, Martubung, Medan Labuhan, Medan, North Sumatra. “Datuk Tongah” is a renowned appellation that has been passed down. This article is an ethnography of my pilgrimage to Keramat Datuk Tongah. The data were obtained through pilgrimage, interviews, observations, and literature review. There are two findings and one recommendation in this article. First, pilgrimage to ancient grave which details are not yet known must to be done on the scientific work. Pilgrimage is a research work, not just a religious ritual. Second, there is a nuance of Aceh in the grave as seen from the headstone, tomb, and decorative patterns. Indeed, the identity of the grave could be found by seeing Aceh as a center of cultural analysis. An insight from irfani or sufistic view entangled for enriching the analysis. The attention needs to be paid by local government in order to preserve Keramat Datuk Tongah and registered it as a tangible cultural heritage.